TANTANGAN LITERASI INFORMASI PETANI DI ERA INFORMASI: Studi Kasus Petani di Lahan Pasir Pantai Daerah Istimewa Yogyakarta - Alia Bihrajihant Raya; Sri Peni Wastutiningsih; Paksi Mei Penggalih; Sylvatra Puspita Sari; Diah Ajeng Purwani (Jurnal Sosial Ekonomi Pertanian (J-SEP), 2017)
Information literacy of farmers is especially significant for the growth of farmer, increasing farmers’ income, promoting efficiency of agriculture and rural development. The aims of this research are getting to know 1) the challenge of farmers to understand the needs, source, access of agricultural information and 2) the challenge of farmers information literacy: possess, syntesize, analyze, diseminate and adoption of agricultural information. Participatory action research was choosen as a tool for enacting farmer-driven research. This result showed that the challenge of understanding the needs of agricultural information are slightly on the low level because farmers have understood the needs of information variety to enhance better farming. They can mention the basic needs of agricultural information on farming in the coastal sandy land which are resistant seed, watering and mulch system, biochemical of fertilizer and pesticide, and market product information. The challenge of farmers information literacy on how the farmers possess, synthesize, analyze, diseminate and adoption of information are demanding. Majority of farmers who called as members of farmer group have merely depended on the information which is provided by the group. They mostly conduct and access agricultural information by using interpersonal approach.